Promotion of seasonal influenza vaccination among staff in residential care homes for elderly in Hong Kong - Chen, H. (Healthc Infect, 2010)
Annual influenza epidemics continue to cause worldwide morbidity, mortality and societal disruption, especially among the aged residents of residential care homes for the elderly (RCHEs). Vaccination remains the most effective measure to prevent influenza and its associated complications. The seasonal influenza vaccine uptake rates among RCHE staff were much lower than that among residents. In order to increase uptake of influenza vaccination among RCHE staff in Hong Kong, this study developed and evaluated amultimodal vaccine promotion program (VPP) based on identified factors affecting vaccination acceptance or refusal within the Hong Kong Chinese context. Vaccine acceptance was found to be significantly associated with belief in vaccine efficacy, duration of service, staff group and providing direct care to residents. The focus group study revealed that RCHE staff's belief in the efficacy and safety of the vaccine played a major role in vaccine acceptance. VPP effectiveness was evaluated with a cluster randomised controlled trial among RCHEs with staff vaccination rates below 50%. Compared with 2008/09, the 2009/10 mean staff vaccination rates increased significantly in both the intervention (39.4% to 59.6% (P < 0.001)) and control groups (36.3% to 47.6% (P = 0.008)). RCHE staff in the intervention group had a higher vaccination rate than in the control group (59.6% versus 47.6%, P = 0.072). This program reinforces the importance of a comprehensive and culturally sensitive approach to promote influenza vaccination for RCHE staff.